Vitamin D deficiency, fatigue, and persistent cough as independent predictors of depressive symptoms in sarcoidosis patients - Gvozdenovic, Branislav; Mihailovic-Vucinic, Violeta; Vukovic, Mira; Omcikus, Maja; Cvejic, Jelena; Belic, Slobodan; Jankovic, Jelena; Djurdjevic, Natasa; Stjepanovic, Mihailo (Journal of Medical Biochemistry, 2025)
Background: Depressive symptoms are frequent in sarcoidosis. We assessed the impact of sarcoidosis symptoms, pulmonary function, fatigue, radiographic findings, comorbidities, treatment, and serum levels of 25-hydroxyvitamin D (25(OH)D) on depressive symptoms in sarcoidosis patients.Methods: In a cross-sectional study we measured depressive symptoms with the Center for Epidemiologic Studies – Depression Scale (CES-D) and fatigue by Fatigue Assessment Scale (FAS). Presence of depressive symptoms was defined with CES-D scores ≥16 and ≥20, respectively. Fatigue was defined with FAS score ≥22.Results: A total of 400 patients were included in the study. CES-D score ≥16 had 128 patients, while CES-D score ≥20 had 86 patients. In a multivariate binomial logistic regression model, the following independent predictors of CES-D score ≥16 were identified: female gender (odds ratio, OR 1.983), chronic sarcoidosis (OR 2.311), serum levels of 25(OH)D ≤20 ng/mL (OR 2.326), persistent dry cough (OR 2.173), FAS Scores ≥22 (OR 9.243), and chest X-ray stage 3 (8.851). Five variables were independent predictors of CES-D score ≥20: diplopia (OR 4.411), FEV1
Keywords: Sarcoidosis, Depressive Symptoms, Vitamin D deficiency, Fatigue, Cough, Multivariate analysis